The modified budgeting system (with special emphasis on the Ministry of Health) / Aida Aris - Aris, Aida (1993)
The main objective of this project paper is to highlight the concept and the practical approach of the Modified Budgeting System in the pilot ministries, which have been selected by the Government to use the system as their main budgeting tool. The second objective is to examine the behavioral aspects of budgeting in the Government sector and the impact of the budgeting system on the actual· users in carrying out their duties and responsibilities. The study will be Ministry of Health made, with special emphasis on the and Hospital Besar Tengku Ampuan Rahimah, Klang, Selangor respectively. The choice of study for the aforesaid agencies are made because of their current involvement in the Modified Budgeting System.